Goldilocks and the three bears - Patience, John (Colour library books England, 1988)
A timeless classic, "Goldilocks and the Three Bears" is a beloved fairy tale that has captivated generations of children. This story follows a curious little girl named Goldilocks as she ventures into the woods and stumbles upon the home of the three bears. Through this enchanting tale, children learn about manners, respect, and the consequences of being too curious.